Microscopic analysis of the deleterious effects of ammonium nitrate fertilizer on concrete. (20th July 2020) - Bibi, Tayyaba; Ali, Amir; Zhang, Jianhua; Naseer, Amjid; Ul Islam, Shams
Highlights: To withstand harsh environment, proper admixtures should be used in concrete. Silica fume enhances concrete strength and resistance towards fertilizer attack. Compressive strength of concrete varies with the variation of silica fume percentage. Silica fume with 8% replacement by weight of cement was found the most efficient. Abstract: This paper presents a detailed study of parameters that makes concrete resistant to ammonium nitrate (NH4 NO3 ) fertilizer attack. The major goal of this research work is to study the effect of ammonium nitrate on the strength and microstructure of silica fume (SF) composite concrete by performing microscopic testing techniques. X-ray diffraction (XRD) & Scanning Electron Microscopy (SEM) were used to study the mineral & chemical compositions of deteriorated samples. Cylindrical specimens were prepared by using silica fume as a partial replacement of cement i.e. 0%, 5%, 8%, and 10% in order to fulfill the requirement of impermeability of concrete specimens towards NH4 NO3. The results show that compressive strength varies with the variation in SF content. Composite Concrete specimens for all percentages of SF were subjected to a 5% solution of NH4 NO3 and its deleterious effect on concrete was accelerated using alternate wetting and oven drying cycles. SEM and XRD results showed the production of calcium nitrate as a product of deterioration. It is concluded that concrete samples with SF content of 8% have shown significant improvement in strength and more resistant to the NH4 NO3 attack as compared to the other samples.